Health Orientation as An Important Principle of the System of Physical Education - Mukhammetov Ahmad (Genius Publishing Group, 2022)
It is known that optimal physical activity in combination with a balanced diet and lifestyle is the most effective in preventing many diseases and increasing life expectancy. Physical exercises provide adaptation of the cardiovascular, respiratory and other systems to the conditions of muscular activity, shorten the duration of functional recovery after changes caused by physical activity, activate and improve metabolism, improve the activity of the central nervous system. In this article, it is written about the health-improving orientation as an important principle of the system of physical education.
Keywords: Physical culture; sports; physical education; students